EVALUASI KOMPETENSI PEDAGOGIK GURU - Erma Erma; Sumadi Sumadi; Sulton Djasmi (Indonesia Journal of Educational Technology, 2013)
The purpose of this study are to describe: (1) Teachers' pedagogic competence in planning SDN 1 Langkapura learning (2) Teachers' pedagogic competence in the implementation of SDN 1 Langkapura learning (3) Teachers' pedagogic competence SDN 1 Langkapura in the evaluation of learning outcomes. The research approach used is an evaluative study. Data was collected through observation and documentation. The data were then analyzed by comparing the data with the categories of research findings that have been made, then do the analysis as a basis for making conclusions.The results on five teacher on SDN 1 Langkapura, that consist of Mardiana Hasra (Mathematic), Ubaidilla Fathurrozi M., S.Pd (Exact Science), Roliyati (Social Science), Erleni, S.Pd. (Indonesian) and Hj. Nurlela, S.Pd. (Citizenship Science), indicate that: (1) Planning of learning by teachers has been implemented in good category, including the clarity of the formulation of learning objectives, materials selection, organizing materials, selection of sources/media learning, scenario clarity, detail of the scenario, the suitability and completeness of the technique by learning an instrument learning. (2) The implementation of learning by teachers has been implemented in good category, which includes the use of method, media and means of learning. School teachers have done to start learning with the introduction, opening, and cover the core activities. (3) Evaluation of learning by teachers has been implemented in good category, which includes the program and implementation of remedial, carry out assessments and implement affective personality assessment of motoric skills.Keywords: evaluation, pedagogic competence